(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe study which carried( The important political development indemocracy Congo).initially deals with The important political events in Africancountry democracy Congo which know tow political period , and this studydivided tow chapter to expend these periods , the first chapter subject was theperiod of mobotow 1965- 1997 . while the second chapter subject was abo democracy Congo under the rule of loran cabeela who’s comes to the rules ofthe African country after he lead military movement agents’ mobotow .but the study have aconcluded that the political development indemocracy Congo happened because of the foreigner role , this role keep theauthority of mobotow and in the end let him down, and he lives the rules andafter that the foreigner role reach loran cabeela to the authority of democracyCongo then he was in struggle with African state which support cabeela in thebeginning , then he killed and his suns Josef came after him.